Strengthening Community Religious Understanding Through Community-Based Religious Study Activities - Arditya Prayogi; M. Adin Setyawan; Riki Nasrullah; Imam Prayogo Pujiono; Moh. Syaifuddin (Sah Publisher, 2026)
Strengthening the community's religious understanding is a crucial need amidst the social dynamics of the digital era, including low self-control and emotional management abilities that impact the quality of individual relationships with others. This community service activity aims to strengthen the understanding and practice of religious values ​​through a public religious study welcoming Ramadan with the theme